Potensi Pengelolaan Sampah dan Limbah Peternakan Berbasis Integrated Resources Recovery Center (IRRC) - Devi Ratna Handini; Rusdiana Setyaningtyas (Publikasi Indonesia, 2026)
Pujon and Ngantang Sub-districts are agrarian–livestock areas in Malang Regency characterized by high generation of municipal solid waste and livestock manure. This study aims to analyze the potential for waste and manure management based on an Integrated Resources Recovery Center (IRRC) using a quantitative–statistical approach to waste generation, waste composition, and livestock waste production data. The methods employed include descriptive statistical analysis, per capita–based waste generation estimation, a seven-day consecutive waste composition survey, and manure production estimation using standard assumptions from the literature. The results indicate that the average municipal solid waste generation reaches 29.22 tons/day in Pujon and 24.55 tons/day in Ngantang, with a dominance of organic waste in Pujon (52.38%) and RDF fractions in Ngantang (40.23%). Meanwhile, the combined manure production of both sub-districts reaches 1,124.54 tons/day, with a realistic recoverable potential of 112.45–224.91 tons/day. These findings confirm that the development of an integrated IRRC system combining composting, RDF production, and manure utilization is technically feasible and strategically important for supporting sustainable environmental management and the implementation of a circular economy in the study area.